1997
DOI: 10.1128/mcb.17.8.4208
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase A-Dependent Phosphorylation Modulates DNA-Binding Activity of Hepatocyte Nuclear Factor 4

Abstract: Hepatocyte nuclear factor 4 (HNF4), a liver-enriched transcription factor of the nuclear receptor superfamily, is critical for development and liver-specific gene expression. Here, we demonstrate that its DNAbinding activity is modulated posttranslationally by phosphorylation in vivo, ex vivo, and in vitro. In vivo, HNF4 DNA-binding activity is reduced by fasting and by inducers of intracellular cyclic AMP (cAMP) accumulation. A consensus protein kinase A (PKA) phosphorylation site located within the A box of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
165
1
9

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(185 citation statements)
references
References 58 publications
10
165
1
9
Order By: Relevance
“…It has been reported that HNF4␣ is under the control of various kinases (PKC and PKA) (38,39) and the role of ERK1/2 in the regulation of HNF4␣ has also been reported (40,41). This latter study suggested that the decreased endogenous HNF4␣ protein level due to various stimuli led to down-regulation of the expression of the target gene.…”
Section: Discussionmentioning
confidence: 48%
“…It has been reported that HNF4␣ is under the control of various kinases (PKC and PKA) (38,39) and the role of ERK1/2 in the regulation of HNF4␣ has also been reported (40,41). This latter study suggested that the decreased endogenous HNF4␣ protein level due to various stimuli led to down-regulation of the expression of the target gene.…”
Section: Discussionmentioning
confidence: 48%
“…We now show that the ligand-induced transactivation of LXR can be regulated in vivo, ex vivo, and in vitro by PKA-dependent phosphorylation. The catalytic subunit of PKA has been identified in the nucleus and phosphorylates numerous transcription factors, modulating their transcriptional activities positively such as hepatocyte nuclear factor-4␣ and negatively such as L-type PK (28). Now, LXR can be added to the list of PKA-modulating factors.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that several nuclear receptors (e.g. estrogen receptor, retinoic acid receptor, peroxisome proliferator-activated receptor, and hepatocyte nuclear factor-4␣) are phosphorylated by PKA leading to modification of their trans activities via diverse mechanism (25)(26)(27)(28). In the current study we investigated effects of cAMP/PKA on the SREBP-1c expression and LXR signaling system.…”
mentioning
confidence: 99%
“…E-cadherin is the first genetic correlation between colorectal cancer and UC, Chimeric mice with impaired E-cadherin function due to expression of dominant-negative N-cadherin developed colitis despite possessing an intact immune system (Hermiston & Gordon 1995a, 1995b. Notably, all of these 4 genes are regulated or related to protein kinases, for example, HNF4alpha-DNA binding activity is dependent on its phosphorylation by protein kinase A (PKA) (Viollet et al, 1997), while its transcription activity was dependent on AMP-activated protein kinase(AMPK) (Hong et al, 2003). Similarly, by GWAS analysis, the strongest association in CD was found in interleukin-12 receptor (IL23R) (Duerr et al, 2006)-as well as the previously identified NOD2 gene.…”
Section: Genetic Factormentioning
confidence: 79%